A Play for Oil The Stories Behind the Discovery and Development of Oil and Gas - Daley, Tim (Springer International Publishing, 2018)
You hold in your hands the most original guide to understanding the oil and gas world - from exploration and production to the related economics and geopolitics. Tim Daley has spent years travelling the world and living as an expatriate in a quest to secure resources and meet humanity's energy demands. After several decades in the hydrocarbon business, he was keen to write a book about his experiences in an easily accessible language, enabling everyone to grasp the technicalities involved in evaluating the resources that lie beneath our feet. If you want to learn how hydrocarbons are discovered and produced, Tim's explanations have the added colour of vivid descriptions of the sites discussed and allow you to meet some of the most important characters in the industry, and to gain new insights into this global industry. In addition, the depictions of key events and locations add an element of national politics and travelogue feel. This book is intended for all members of the general public interested in how hydrocarbon resources are discovered, providing a concise account of how oil geologists view the subsurface, and illustrated by the author's personal experiences in countries around the world. The book will also be of interest to ex-oil industry workers, allow geologists to compare the author's experiences to their own, and provide non-geologists essential insights into how the oil is won. Written in an informal style, it makes for a relaxing yet informative reading experience.